Determination of Hydraulic Conductivity for Pure Gravel, Pure Sand And Grain Mixtures - Farahin Kamaruddin, Siti; Zafyrah Mohd Zahid, Azyan; Seitz, Lydia; Kassim, Jalina (International Journal of Engineering and Technology, 2018)
The colmation process which describes the infiltration of fine sediments into the river beds is prominent for many years. However, due to the lack of knowledge and the absence of specific parameters, the colmation cannot be properly described. Therefore, hydraulic conductivity can be a virtuous way to describe this process. The aim of this study is to determine the hydraulic conductivity of gravel and sand mixtures. By using the KSAT device, hydraulic conductivity values from the laboratory samples were determined. Based on the data obtained from the experiment, the threshold of grain size distribution and hydraulic conductivity for the laboratory samples were established. The results show that when there is high percentage of coarse particle in a mixture compared to the percentage of the fine particle, the value of hydraulic conductivity tends to increase.Â Â